Impact of Personal Protective Equipment on the Quality of Chest Compressions in Prehospital Care: A Prospective Randomized Crossover Study. Issue 1 (February 2023) - Cmorej, Patrik Christian; Hrach, Karel; Argayova, Ivana; Peran, David; Pekara, Jaroslav; Jarabicova, Olga; Kelbich, Petr; Spicka, Jan; Ralbovska, Dana Rebeka
Abstract: Introduction: The use of personal protective equipment (PPE) in prehospital emergency care has significantly increased since the onset of the coronavirus disease 2019 (COVID-19) pandemic. Several studies investigating the potential effects of PPE use by Emergency Medical Service providers on the quality of chest compressions during resuscitation have been inconclusive. Study Objectives: This study aimed to determine whether the use of PPE affects the quality of chest compressions or influences select physiological biomarkers that are associated with stress. Methods: This was a prospective randomized, quasi-experimental crossover study with 35 Emergency Medical Service providers who performed 20 minutes of chest compressions on a manikin. Two iterations were completed in a randomized order: (1) without PPE and (2) with PPE consisting of Tyvek, goggles, KN95 mask, and nitrile gloves. The rate and depth of chest compressions were measured. Salivary cortisol, lactate, end-tidal carbon dioxide (EtCO2 ), and body temperature were measured before and after each set of chest compressions. Results: There were no differences in the quality of chest compressions (rate and depth) between the two groups (P >.05). After performing chest compressions, the group with PPE did not have elevated levels of cortisol, lactate, or EtCO2 when compared to the group without PPE, but did have a higher body temperature (P <.001). Conclusion: The use of PPE during resuscitation did not lower the quality of chest compressions, nor did it lead to higher stress-associated biomarker levels, with the exception of body temperature.